Hubungan Antara Pola Asuh Ibu Bekerja Dan Tidak Bekerja Dengan Kepercayaan Diri Anak Di TK Purbonegaran Sagan Yogyakarta - Hanna Juliana Sinaga, Lely Lusmilasari dan Fitri Haryanti (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Sometimes ago child mothering generally done by mother because they are not work. Nowdays, at the height of education of woman and demand of live the effect of monetary crisis that was made mother work to earn life. Mother with child of preschool ought to be correct how to lead time prudently, because the basic in raising child personality especially self confidence was at preschool. The problem is how mothering applied by mother to their children so that the child growing up to become strong and stabilize person, with high self confidence.Objective: The aim of this research is knowing whether there are difference mothering style between working and not working mother with the growing up child's self confidence. Methods: This research was an quantitative method by using cross-sectional design.The analysis of the data was using Chi-square. This research was doing to ward 51 couples of mother and their child which is studying in TK Purbonegaran Sagan Yogyakarta, 43 respondents is fulfilling criterion divided in two group that is working mother 17 people (39,5%) and not working mother 26 people (60.5%). Data collecting by using questionnaire consisted of respondent identity, mothering style questionnaire, and child's self confidence questionnaire.Results: The result of this research showing there was no significant difference of mothering style between working and not working mother (p > 0,05). There was difference of child's self confidence between working and also not working mother (p < 0,05). There was significant difference of child's self confidence between autoritarian, permissive, and authoritative pattern (p < 0,05). There was no difference of mothering style between working and not working mother with the growing up the child's self confidence divided in social interaction aspect, independence aspect, and also tolerance aspect (p > 0,05).Conclusion: The categorizing of child's self confidence shows that mostly child have middle category with autoritative pattern, and mostly child have middle category of child's self confidence with not working mother.Keywords: child's self confidence, mothering style, working mother, not working mother